Effectiveness of the Implementation of the Non-Cash Food Assistance Program (BPNT) and the Family Hope Program (PKH) on the Welfare of the Monta Baru Village CommunityDompu Regency - Ilham, Ilham; Samsudin, Samsudin; Sumarni, Sumarni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the impact of the Non-Cash Food Assistance Program (BPNT) and the Family Hope Program (PKH) on community welfare in Monta Baru Subdistrict, Dompu Regency. The multidimensional nature of poverty serves as the primary background for this study, highlighting the role of social assistance in reducing the economic burden of the community. A quantitative approach was employed, using a survey method with a Likert, scale questionnaire administered to 86 respondents who are Beneficiary Families (KPM). Data analysis was conducted using descriptive statistics, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression. The findings indicate that both BPNT and PKH have a significant influenceboth simultaneously and partiallyon community welfare, with PKH contributing more dominantly than BPNT. The coefficient of determination (R²) value of 32.1% suggests that these two programs play an important role in improving welfare, although other external factors also contribute. These findings imply that the effectiveness of social assistance programs must be supported by accurate data, ongoing mentoring, and active community participation in order to achieve inclusive and sustainable welfare.